DIABETIC FOOT ULCERS: IDENTIFICATION, DIAGNOSIS AND CURE - Saha, *Anirban; Halder, Sukanya; Kumar Giri, Navneet (International Journal of Ayurveda and Pharma Research, 2016)
Diabetic foot ulcers (DFUs) are a fairly common complication of diabetes. There are two forms: neuropathic ulcers and ischemic ulcers, although most DFUs are a mixture of both. Neuropathic Diabetic Foot Ulcers may come about because high blood sugar levels damage the nerves in your legs (called peripheral neuropathy). This means you are less likely to feel when you have injured your foot. The injury may be something as small and insignificant as a blister or a cut from walking with a stone in your shoe. If you cant feel the pain, then you do not know the injury is there and wont protect it and avoid walking on it. This makes it hard for the wound to heal. People with diabetes often suffer from poor blood circulation, especially to the legs (as part of a wider circulation problem called peripheral vascular disease). This means that it takes longer for your foot wounds to heal than for people with normal blood flow. This is Ischemic Diabetic Foot Ulcer. If a wound cannot heal, it is called an ulcer and it can become very serious. A diabetic foot ulcer presents a perfect way for germs and infection to enter your body. Infection can spread via the blood stream and enter into your bones. When this happens, the best, although drastic, action is to amputate the affected limb to stop gangrene spreading throughout your body. In the US and the UK, around half of all amputations are related to diabetes. Around half of people who have a leg amputated due to diabetes die within 5 years of the operation. This wouldnt need to happen if we had better foot care. Diabetic foot ulcer is one of the long standing complications of diabetic mellitus with the life time risk up to 25%. Many of the etiological factors contributing to the formation of diabetic foot ulceration may be identified using simple, inexpensive equipment in a clinical setting. Appropriate wound care for diabetic patients addresses these issues and provides optimal local ulcer therapy with debridement of necrotic tissue and provision of a moist wound-healing environment. The pathogenesis of foot ulceration is complex, clinical presentation variable, and management requires early expert assessment. Interventions should be directed at infection, peripheral ischemia and abnormal pressure loading caused by peripheral neuropathy and limited joint mobility.